Tribological properties of WS2 thin films with improved adhesion using MAIP/HiPIMS composite deposition - Jianjian Yu; Ping Zhang; Puyou Ying; Chen Li; Changhong Lin; Tao Yang; Jianbo Wu; Tianle Wang; Nikolai Myshkin; Vladimir Levchenko (Journal of Materials Research and Technology)
Dense WS2 thin films with excellent self-lubricating properties have been prepared using high-power impulse magnetron sputtering (HiPIMS) successfully. Nevertheless, the films as-deposited exhibits poor wear resistance under high-frequency service conditions due to poor adhesion. Here, a composite deposition technique combining multi-arc ion plating (MAIP) and HiPIMS was used to prepare WS2 thin films. Compared to only using HiPIMS, MAIP/HiPIMS composite deposition significantly improved the adhesion of the films, with the critical load LC3 increasing from 18 N to over 60 N. Correspondingly, the wear resistance performance of the films was enhanced at higher sliding frequencies with a reduce of six- ∼ seven-fold. Analysis has found that improving the adhesion can reduce adhesive wear at high sliding frequencies, thereby enhancing wear resistance. However, due to droplet defects introduced by MAIP, abrasive wear increases and wear resistance deteriorates under high loads.